2016
DOI: 10.1103/physrevb.94.024517
|View full text |Cite
|
Sign up to set email alerts
|

Correlation-drivend-wave superconductivity in Anderson lattice model: Two gaps

Abstract: We present the full Gutzwiller-wave-function solution of the Anderson lattice model in two dimensions that leads to the correlation-driven multigap superconducting (SC) ground state with the dominant d x 2 −y 2 -wave symmetry. The results are consistent with the principal properties of the heavy-fermion superconductor CeCoIn5. We regard the pairing mechanism as universal and thus applicable to other Ce-based heavy-fermion compounds. Additionally, a gain in kinetic energy in the SC state takes place, as is also… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 64 publications
0
28
0
Order By: Relevance
“…To account for nonlocal spatial correlations in finite dimensions, higher orders of the expansion (k > 0) are systematically incorporated in Eq. (4) and expectation values of the products of the operators are evaluated diagrammatically [25,26,[42][43][44][45][46][47]. By construction [25], the convergence of the sum with respect to k is reached relatively quickly, and here we found that k = 4 is already satisfying (see the Supplemental Material [48]).…”
mentioning
confidence: 81%
“…To account for nonlocal spatial correlations in finite dimensions, higher orders of the expansion (k > 0) are systematically incorporated in Eq. (4) and expectation values of the products of the operators are evaluated diagrammatically [25,26,[42][43][44][45][46][47]. By construction [25], the convergence of the sum with respect to k is reached relatively quickly, and here we found that k = 4 is already satisfying (see the Supplemental Material [48]).…”
mentioning
confidence: 81%
“…By the same token, one expects the Kondo-like term to contribute to inter-orbital pairing (e.g. c † f † [43]), which plays an important role in unconventional superconductivity [44,45] in the context of heavy fermion materials, such as CeCoIn 5 [23,25,43,46,47]. However, here we are dealing with well localised magnetism, such as Tm, Er and Ho-based materials, so that the contribution from unconventional channels may be disregarded in a first approach.…”
Section: Model and Methodsmentioning
confidence: 99%
“…(2), is a complex many-body problem and may be carried out for finite systems by variational Monte-Carlo methods (see., e.g., [22]) or in thermodynamic limit by suitable diagrammatic-expansion. [23][24][25] Within the latter framework, eliminating Hartree-bubbles improves substantially series convergence and is achieved by imposing an additional constraint 23,26P 2…”
Section: Model and Methodsmentioning
confidence: 99%